Measuring the natural rate of interest after COVID-19 - Kathryn Holston; Thomas Laubach; John C. Williams (Federal Reserve Bank of New York, 2023)
We modify the Laubach-Williams and Holston-Laubach-Williams models of the natural rate of interest to account for time-varying volatility and a persistent COVID supply shock during the pandemic. Resulting estimates of the natural rate of interest in the United States, Canada, and the Euro Area at the end of 2022 are close to their respective levels estimated directly before the pandemic; that is, we do not find evidence that the era of historically low estimated natural rates of interest has ended. In contrast, estimates of the natural rate of output have declined relative to those projected before the pandemic.
Keywords: C32; E43; E52; O40; 330; natural rate of output; time-varying volatility; Kalman filter; trend growth; COVID-19pandemic